Slow Stain - Wait, Hester Sophia (Michaelis School of Fine Art, 2024)
My research consists of artwork and an explicatory document. They explore forms of subtle violence against women in the domestic space that are easily overlooked by society. The artwork is comprised of works concerning familiar aspects of the feminine disrupted in some way as in interpretation of insidious violence in domestic space. This violence is not restricted to physical acts, but extends to psychological and emotional abuse. In this document, I will demonstrate that the latter forms of ill treatment often occur within the domestic space and can be inadvertently aimed at women and young girls, which I attribute to various forms of social conditioning. These forms of cruelty are often subtle and can easily go unnoticed, even by those directly involved. I reference my own middle class, white Afrikaner heritage and experience, which potentially will resonate with others despite my specific experience as certain similarities may be found across many cultural contexts. In this document I look at the history of patriarchy and the impact of 'otherness' and gender binaries as contributory factors to a form of damaging, subtle and disempowering violence that French sociologist and anthropologist Pierre Bourdieu articulated as 'symbolic violence' - 'the violence which is exercised upon a social agent with his or her complicity' (Bourdieu and Wacquant 1992: 167). Extending this, I consider the serious emotional impact that 'symbolic violence' can have on an individual and the long lasting psychological effects that may follow, even when no physical damage appears evident. I also investigate the suppression of women in specific relation to the construction of femininity in the family, the position of women in contemporary society and my own experiences. The area of focus within my research is that of the home and domestic environment, a space that usually signifies comfort and safety, but can be destabilised by subtle forms of trauma and oppression, often experienced subliminally. While I do not always discuss the acts that allow for this, I do consider their aftermath by using my own position as a single Afrikaner woman as a starting point. Furthermore, by examining ideas around patriarchy and the 'othering' that can result from gender binaries, I consider how these ideas aid an understanding of the ways in which symbolic violence is 'handed down' through generations and backed up by a patriarchal society, culture and media. I demonstrate that this has allowed forms of symbolic violence to infiltrate society so gradually that it has become invisible. By referring to my own personal experiences, I elaborate on how women may accept their role as the binary opposite of men, become 'complicit' in accepting these roles. They can thus be placed as an 'other' in relation to male-dominated roles, especially in certain cultures and families that consciously or unconsciously align themselves with patriarchal ideas. By exploring such subtle and everyday forms of violence against women I hope to highlight violence against women and draw attention to how women experience slow, symbolic violence through gender stereotypes and false perceptions that women are no longer male-dominated. With all of this in mind, this body of work is an exploration of aspects of being a woman within the sphere of the domestic space and the expectations that can accompany this. Through my practice of making time-consuming hand work characteristic of women's craft, I aim to evoke the subtle oppression and 'symbolic violence' that occurs within the home. These works include sentimental hand-embroidered pieces, life-sized sculptural forms and obscured stained paintings that invite affection, suggest comfort, and encourage incomprehension, but also anxiety and pity